Reisen bildet. Eine Mobilitätsmaßnahme zur Kompetenzentwicklung des wissenschaftsunterstützenden Personals - Thomas Crowe; Tanja Kromer (Personal- und Organisationsentwicklung in Einrichtungen der Lehre und Forschung (P-OE), 2021)
– Mobility is an integral part of careers in science - whether as a langer research stay abroad or an intersectoral excursion into industry, politics or administration. The professionalization of the entire research support sector is advancing, and so the question also arises as to suitable personnel development measures that can be used to further develop employees in infrastructure, administration and research management. In this article, and by drawing on practical experience at the WZB Berlin Social Science Center, we demonstrate how an ambitious mobility scheme for the research support staff can be brought to life.
Keywords: 330